The effects of maternal employment on adolescent adjustment - Yıldızlı, Alin Sarı. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1993., 1993)
The purpose of this study was to investigate the effects of maternal employment on the sex-typed characteristics, perception of the family environment and adjustment of adolescents from a sample of intact Turkish families. The sample was composed of 107 adolescent students whose mothers were employed full-time and 107 students whose mothers were full-time homemakers. The measurement instruments were the SexTrait Stereotype Measure, the Family Environment Questionnaire and the Minnesota Counseling Inventory. It was hypothesized that adolescents whose mothers were working would have less sex-typed characteristics than adolescents whose mothers were full-time homemakers. Also, no difference was expected in perception of the family environment between adolescents whose mothers were working and those whose mothers were full-time homemakers. It was also hypothesized that there would be no differences in level of adjustment between adolescents whose mothers were working and adolescents whose mothers were full-time homemakers. The findings revealed that maternal employment status by itself was not a significant factor affecting adolescents' sextyped characteristics, perception of the family environment and adjustment. However, interaction of maternal employment by gender was a significant factor affecting adolescents' adjustment, as were perceived family environment, sex-typed characteristics and gender.
Keywords: Mothers -- Employment.; Working mothers.